Agriculture in Brazil's Southeast region: Limitations and future challenges to development - César Nunes de Castro (Institute for Applied Economic Research (ipea), 2015)
Much of the recent dynamism of the Brazilian agricultural sector occurred in activities developed in Brazil's South, Southeast and Midwest regions. Specifically, the Southeast region was responsible in 2006 for approximately 34% of the value of agricultural production according to data from the 2006 Agricultural Census. The aim of this study is to assess the recent situation of agriculture in the Southeast, based on data from the 2006 Agricultural Census. Based on this diagnosis, the study aims to identify constraints to agricultural development in the region and discuss measures that can contribute to the expansion of regional agricultural production with the generation of jobs and income for the population. Among these may be mentioned some measures: improvement in logistics infrastructure; social development of rural areas through mechanisms of generating income for family farmers; the agricultural research in the region needs to provide solutions for further development of farming, promotion of productive associations, among others.
Keywords: Q1; Q10; 330; agriculture; livestock; Southeast region; development